Genotypic characterisation of vancomycin-resistant Enterococcus faecium isolates from haemato-oncological patients at Olomouc University Hospital, Czech Republic - Kolar, M; Pantucek, R; Vagnerova, I; Kesselova, M; Sauer, P; Matouskova, I; Doskar, J; Koukalova, D; Hejnar, P (Clinical microbiology and infection, 2006)
This study describes the first molecular characterisation of clinical isolates of vancomycin-resistant enterococci (VRE) in the Czech Republic. Of 2647 patient isolates of Enterococcus spp. from 1997-2002, 121 (4.6%) were identified as VRE. The most common isolates were VanA+ Enterococcus faecium (78%) and VanB+ Enterococcus faecalis (10%). In addition, five VanA+ E. faecium isolates were obtained from environmental and staff sampling. Macrorestriction analysis of SmaI restriction fragment length polymorphism was performed for 54 VanA+ E. faecium clinical isolates and the five VanA+ E. faecium environmental isolates. Thirty-two unique restriction endonuclease patterns were identified, including two predominant clonal types represented by five or more isolates. Two environmental VanA+ E. faecium isolates were closely related to two patient isolates, which had an identical SmaI macrorestriction pattern. The results indicated potential survival of strains in the hospital environment and possible subsequent transmission to hospitalised patients.
Keywords: Vancomycin Resistance; Neoplasms; onkologická péče - zařízení; hematologické nádory; infekce spojené se zdravotní péčí; Genotype; Hematologic Neoplasms; Česká republika; rezistence na vankomycin; Enterococcus faecium; Czech Republic; lidé; grampozitivní bakteriální infekce; Cross Infection; Gram-Positive Bacterial Infections; Humans; Cancer Care Facilities; polymorfismus délky restrikčních fragmentů; Enterococcus faecalis; genotyp; nádory; Polymorphism, Restriction Fragment Length